Uji Teratogenik Air Rebusan Mie Instan Selama Masa Kehamilan Mencit Betina (Mus musculus L.) Melalui Pengamatan Kelainan Morfologi Fetus: Teratogenic Test of Instant Noodle Water During the Pregnancy of Female Mice (Mus musculus L.) through Observation of Fetus Morphological Disorder - Sister Sianturi; Annisa Farida Muti; Moh. Benny Perdana (Jurnal Sains dan Kesehatan, 2020)
Indonesia is one of the second ranked countries in the world consuming the most instant noodles. This product is liked by all people, especially pregnant women, so research is needed to determine the effect of consumption of instant noodles on fetal development. This study uses mice as a test animal. The purpose of this study was to determine the teratogenic effects of instant noodle cooking water on pregnant mice (Mus musculus L.) concentrations of 30%, 50%, and 70% based on morphological observations of fetal mice during pregnancy. This research is experimental with a completely randomized design (CRD) method using 60 experimental female mice in pregnancy divided into 10 groups, 1 group was given aquadest as a control group and 9 groups were given instant noodle cooking water in 3 different brands with a concentration of 30% , 50%, and 70% given on the 6th day of pregnancy until the 15th day of pregnancy. Then on the 18th day female mice were sacrificed by dislocation of the neck to see the teratogenic effects based on morphology in the fetus. The results of the statistical test showed that there were differences in the average number of dead fetuses in each group (p = 0.05), differences in body weight (p = 0.0001), and body length (p = 0.0001) and found one fetuses that experience cleftpalate or abnormalities in the palate of the fetus of mice in the treatment of instant noodle boiled water concentration of 70%